The Effect of Current Ratio, Debt to Equity Ratio, and Return on Equity on Banking Stock Prices (IDX 2022-2024) - Andini Ayu Pratiwi; Enny Istanti; Nurul Iman (Universitas Bhayangkara Surabaya, 2026)
This study aims to analyze the effect of Current Ratio (CR), Debt to Equity Ratio (DER), and Return on Equity (ROE) on stock prices of banking companies listed on the Indonesia Stock Exchange (IDX) during the 2022-2024 period. This research employs a quantitative approach with multiple linear regression analysis. Purposive sampling was applied based on specific criteria, resulting in 10 banking companies as research samples. Secondary data was obtained from annual financial statements and closing stock prices published by IDX, with 30 observations collected over the 2022-2024 period. The results indicate that CR, DER, and ROE simultaneously have a significant effect on stock prices (F-count = 3.559, Sig. = 0.028). However, partially, only ROE has a positive and significant effect on stock prices (β = 0.556, p = 0.004), while CR (β = -0.050, p = 0.787) and DER (β = -0.027, p = 0.878) do not have significant effects. ROE emerges as the most dominant variable influencing stock prices. These findings indicate that investors in the banking sector place greater emphasis on profitability compared to liquidity and capital structure in making investment decisions.